An evaluation of the impact of the key information summary on GPs and out-of-hours clinicians in NHS Scotland. Issue 3 (August 2015) - Craig, Joyce; Morris, Libby; Cameron, Jonathan; Setters, Jo; Varley, Danielle; Lay, Anna; Thompson, Ian
Background and aims: Key information summary is one of the first national shared electronic patient records enabling GPs to share clinical information with unscheduled care providers, including out-of-hours. Implemented during 2013, over 90, 000 patient records have been created. This evaluation identified the impact of key information summary on healthcare services. Methods: Evidence was collected using online questionnaires and structured telephone interviews. Opinions providing a numerical estimate of value were analysed using statistical methods, while qualitative responses were synthesised using thematic analysis. Results: The vast majority of respondents from 441 GP practices and 33 out-of-hours clinicians show that key information summary enhances patient safety, improves clinical management, reduces hospital admissions, empowers clinicians, aids communication across services and enables decisions to be responsive to patients' wishes. Conclusions: Patients willingly consent to share data with unscheduled care clinicians. Patients benefitting include those with palliative, complex or multiple conditions, at high risk of using emergency services. Out-of-hours clinicians would welcome more key information summaries, all well-completed and including social care information. Improvements include software enhancements and wider sharing of information with all unscheduled care services.